(untitled) - REZHA F, RIA (Jurnal Ilmu Manajemen (JIM), 2013)
This research was aimed to analyze the influence ofeconomic value added, residual income, earnings and cash flowfrom operations on stock returns of the telecommunicationcompanies listed in BEI simultaneously and partially. This researchused quantitative approach and secondary data sources. By usingpurposive sampling, the population was the telecommunicationcompanies listed in BEI and five companies were selected to beresearch samples. The result showed that simultaneously allindependent variables had significant influence on stock returns.While partially independent variables, namely EVA, earnings andcash flow from operations had significant influence on stock return.However, only residual income had significant negative.Keywords: economic value added (EVA), residual income, earnings, cash flow from operations, stock returns.